Slovenija v evroatlantskih integracijah - Horvat, Marjan (Annales. Series historia et sociologia, 2020)
Based on the conceptual images of the "vanishing mediator" (F. Jameson and E. Balibar) and proceeding from the definition of its passive and active principles, the paper examines the previous, current, and potential roles of Slovenia in Euro-Atlantic integrations. Developing these starting points, the author first analyses the specifics of Slovenian adoption/adaptation of the European integration discourse prior to Slovenia's accession to the European Union, analysing in a second step the imbalances in development in post-crisis Europe, both with the purpose of comparatively determining Slovenia's position and potential as a "small state" at regional, European, and international levels. In this, the author focuses mainly on the issue of the "normative power" of Slovenia in the international arena, exploring, however, the foreign policy potential of the state through the perspective of the formation of identity and discourse patterns of Slovenianhood. The premise is that with Slovenias accession to the European Union (and NATO) the "original" Slovenian idea of multinational integration - presented in this paper largely through an analysis of treatises about the advantages and disadvantages of the memberships, published in the years preceding the accession - was "passivized"; however, unlike the eastern and central European countries, which underwent a shock therapy during the period of transition, Slovenia preserved its own view of the objectives and goals of European integration. In the context of the development of European integration discourse, presenting the experience of eastern European countries with European integration, and the relations in post-crisis Europe, the paper thus analyses what marks the "distinctiveness" of the Slovenian experience, comparatively. The latter is defined based on socio-constructivist theories, theories of ethno-nationalism, and political science studies of small states. Relying on these findings, the paper substantiates the specific identity and discursive patterns of Slovenianhood and explores the possibilities of their "translation" into a foreign policy strategy - emphasising, nevertheless, that the success of foreign policies based on the "normative power" of small states depends on the understanding that these basically address a socio-developmental issue and not only a foreign policy issue.
Keywords: European integration; European Union; Evropska unija; evropske integracije; foreign policy; integrazione Europea; politica estera; post-crisi; post-crisis; post-kriza; Slovenia; Slovenija; Unione Europea; zunanja politika